2016
DOI: 10.1038/srep38504
|View full text |Cite
|
Sign up to set email alerts
|

The Core Subunit of A Chromatin-Remodeling Complex, ZmCHB101, Plays Essential Roles in Maize Growth and Development

Abstract: ATP-dependent chromatin remodeling complexes play essential roles in the regulation of diverse biological processes by formulating a DNA template that is accessible to the general transcription apparatus. Although the function of chromatin remodelers in plant development has been studied in A. thaliana, how it affects growth and development of major crops (e.g., maize) remains uninvestigated. Combining genetic, genomic and bioinformatic analyses, we show here that the maize core subunit of chromatin remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The chromatin remodeling complexes play a vital role in regulating chromatin structure and assembly, the dynamic nature of chromatin, DNA methylation, and histone modification (Ho and Crabtree, 2010). In maize, CHB101 is involved in maintaining nucleosome density and chromosome structure (Yu et al, 2016). In Arabidopsis, the SWI3 proteins may alter the interaction between the histones and DNA to affect plant development and transcription (Sarnowski et al, 2005;Zhu et al, 2013).…”
Section: The Chromatin Remodeling Complex Plays a Potential Role In Rmentioning
confidence: 99%
“…The chromatin remodeling complexes play a vital role in regulating chromatin structure and assembly, the dynamic nature of chromatin, DNA methylation, and histone modification (Ho and Crabtree, 2010). In maize, CHB101 is involved in maintaining nucleosome density and chromosome structure (Yu et al, 2016). In Arabidopsis, the SWI3 proteins may alter the interaction between the histones and DNA to affect plant development and transcription (Sarnowski et al, 2005;Zhu et al, 2013).…”
Section: The Chromatin Remodeling Complex Plays a Potential Role In Rmentioning
confidence: 99%
“…Previously, we reported that ZmCHB101 may regulate the expression of genes involved in nitrogen compound metabolic process (Yu et al, 2016). To investigate this possibility, the seeds of WT plants and ZmCHB101-RNAi lines were incubated on moist filter paper at 28°C for 3 days to allow germination.…”
Section: Zmchb101 Regulates Nitrate-induced Lateral Root Formation Anmentioning
confidence: 99%
“…ZmCHB101-RNAi lines, RS1 and R101, have been described previously (Yu et al, 2016), in which ZmCHB101 transcript levels were approximately 7% and 16% of that in the WT, respectively. Seeds of the WT and ZmCHB101-RNAi lines were sterilized using 1% sodium hypochlorite and incubated on moist filter paper at 28°C for 3 days for germination.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations